2020
DOI: 10.1038/s41598-020-60718-8
|View full text |Cite
|
Sign up to set email alerts
|

Jawbone remodeling: a conceptual study based on Synchrotron High-resolution Tomography

Abstract: one of the most important aspects of bone remodeling is the constant turnover mainly driven by the mechanical loading stimulus. the remodeling process produces changes not only in the bone microarchitecture but also in the density distribution of the mineralized matrix-i.e. in calcium concentrations-and in the osteocyte lacunar network. Synchrotron radiation-based X-ray microtomography (microCT) has proven to be an efficient technique, capable to achieve the analysis of 3D bone architecture and of local minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
3
17
0
2
Order By: Relevance
“…The increasing in terms of mineralized volume of the BCP-based Testsample was correlated to the study of bone architecture at the length-scale pertaining the observation of the osteocyte lacunar network; the same subvolumes investigated for producing the microarchitecture data were also studied for the osteocyte lacunae 3D morphometric analysis (Table 2B): considering the standard deviations, comparable values in Test and in Control sites (both Pd-Ctr and UnL-Ctr), when evaluating Lac.V, Lac.Th, and Lac.Nr. However, the observation of the pure mean values, revealed the same values in Test-sample and the UnL-Ctr samples in terms of lacunar density (Lac.Nr), but an increased mean Lac.Nr in the physiological context of the peri-dental site (Pd-Ctr), in agreement with previous observations (Iezzi et al, 2020).…”
Section: High-resolution X-ray Tomographysupporting
confidence: 92%
See 3 more Smart Citations
“…The increasing in terms of mineralized volume of the BCP-based Testsample was correlated to the study of bone architecture at the length-scale pertaining the observation of the osteocyte lacunar network; the same subvolumes investigated for producing the microarchitecture data were also studied for the osteocyte lacunae 3D morphometric analysis (Table 2B): considering the standard deviations, comparable values in Test and in Control sites (both Pd-Ctr and UnL-Ctr), when evaluating Lac.V, Lac.Th, and Lac.Nr. However, the observation of the pure mean values, revealed the same values in Test-sample and the UnL-Ctr samples in terms of lacunar density (Lac.Nr), but an increased mean Lac.Nr in the physiological context of the peri-dental site (Pd-Ctr), in agreement with previous observations (Iezzi et al, 2020).…”
Section: High-resolution X-ray Tomographysupporting
confidence: 92%
“…However, this Testsample did not participate in mastication for 7 years; thus, it was particularly interesting to study possible alterations with the physiological conditions of the peri-dental bone (Pd-Ctr) and with unloaded controls (UnL-Ctr), (i.e., with bone biopsies spontaneously healed in 12 months after tooth extraction but not participating in mastication). This comparative study, shown in Tables 2A,B, was supported by the data of a recent study (Iezzi et al, 2020). Table 2A showed such comparison in terms of microarchitecture quantitative study: it was observed that the Test-sample turned out to be much more mineralized and bulky not only compared to UnL-Ctr, with an increase of the mineralized volume of 121%, but also compared to the peri-dental physiological context (Pd-Ctr), with an increase by over 61%.…”
Section: High-resolution X-ray Tomographysupporting
confidence: 87%
See 2 more Smart Citations
“…In this context, several computer-aided imaging techniques were used to investigate the microarchitecture of BSBs; in particular, the gold standard for a reliable 3D examination is based on high-resolution X-ray computed tomography (microCT). MicroCT was not only successfully used to reconstruct the morphometry of bone tissue at different length-scales [ 20 , 21 , 22 , 23 , 24 ] and in different environmental and genetic contexts [ 25 , 26 , 27 , 28 ], but it is nowadays the elective technique for the characterization of biomaterials used in bone tissue engineering [ 29 ] and also in dental districts [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%